(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The use of services, especially Web services, became a common practice. In Web services, standard communication protocols and simple broker-request architectures are needed to facilitate exchange of services, and this standardization simplifies interoperability. In the coming few years, services are expected to dominate software industry. Web Services use Extensible Markup Language (XML) messages. In addition to the data exchange standard XML, three new standards Simple Object Access Protocol (SOAP); Web Services Description Language (WSDL); and Universal Description, Discovery and Integration (UDDI) let Web services talk to one another. Each Web service is described by Web Service Definition Language (WSDL) and their interactions with other services are described by Web Service Choreography Interface (WSCI). There are increasing amount of Web services being made available in the Internet, and an efficient Web services composition algorithm would help to integrate different algorithm together to provide a variety of services. This paper mainly concentrates on the Web service composition algorithm provided earlier. The algorithm is dynamic, deadlock free and also efficient than other algorithms. However, it has to compose the component each and every time the web service is requested. This has a serious effect when there a component is requested frequently. Hence to overcome the problem we have given a new innovative idea using the cache proxy servers combining both the static and dynamic approach making a performance in the previously given approach and the paper is going to explain the same.